Pseudociência no ensino: análise das percepções e posturas de professores da área de ciências da natureza - Jesus, Atair José Bernardino de (Universidade Federal de São Carlos, 2026)
Pseudoscience consists of a body of ideas and practices characterized by difficult demarcation; it presents itself through explanations with a scientific appearance, yet fails to meet the fundamental criteria that characterize the production of scientific knowledge, such as testability, falsifiability, critical analysis, and peer validation. Beyond the difficulties regarding its definition, pseudoscience exhibits recurrent characteristics identified in the literature, such as a tendency to present itself as an alternative or superior form of knowledge, exploiting the limitations, uncertainties, and errors of science itself to challenge its credibility. These theories frequently gain traction by offering simplified and emotionally appealing explanations for complex phenomena, in contrast to science, which is characterized by the constant revision of hypotheses, critical analysis, and falsifiability. Adherence to pseudoscientific beliefs is also linked to cognitive predispositions that favor pattern-seeking, simple explanations, and a sense of control in the face of uncertainty. In this context, pseudoscience produces impacts that transcend the epistemological realm, affecting decisions related to health, social life, and education, particularly within a landscape marked by the widespread circulation of information and the dissemination of misinformation in digital environments. Although not a recent phenomenon, its presence has intensified across different social contexts, especially through conspiracy theories and anti-scientific discourses in digital media. This scenario became particularly evident during the COVID-19 pandemic, when pseudoscientific explanations and false information vied for space with established scientific knowledge on topics related to public health, vaccination, and disease prevention. Given this context, schools assume a significant role in promoting scientific literacy and critical thinking, leaving teachers to mediate between scientific knowledge and the discourses circulating in society. This research investigates the perception of K-12 Natural Sciences teachers regarding pseudoscience and its presence in education. It stems from the understanding that how educators comprehend, interpret, and position themselves toward pseudoscience can directly influence both classroom pedagogical practices and students' scientific development. The investigation was guided by the following research questions: How do K-12 Natural Sciences teachers perceive pseudoscience in education? What teacher positioning profiles regarding pseudoscience can be identified based on these teachers' perceptions? As a general objective, this study sought to analyze how K-12 Natural Sciences teachers perceive pseudoscience in education. Specifically, it aimed to identify and characterize teacher positioning profiles regarding pseudoscience based on the stances assumed by teachers within the context of Natural Sciences education; analyze the conceptions of pseudoscience held by these educators; and investigate how they self-identify in relation to pseudoscience. For data collection, the Investigative Questionnaire on the Perception of Pseudoscience in Natural Sciences Education (QIPPECN) was developed by the author in collaboration with the Research Group on Science Teaching and Communication (GPEDiC). The instrument was administered in a virtual environment via the Survio platform, with the participation of 178 K-12 teachers working across different educational stages, from Early Childhood Education to High School, spanning various regions of the country. Although it engaged participants from different cities and regions, the study does not claim statistical representativeness of the national teacher population. The research adopted a mixed-methods approach using elements of Content Analysis (CA), descriptive statistics, and inferential statistics, with emphasis on Exploratory Factor Analysis (EFA) and Spearman's correlation coefficient (ρ). The results indicate that most participants recognize pseudoscience as a domain distinct from science and reaffirm the centrality of scientific knowledge in Natural Sciences education. However, the data also reveal the coexistence of diverse teacher positions regarding the phenomenon, including perspectives aimed at critically confronting pseudoscience, neutral stances, and attitudes of omission, which may be associated with professional insecurity and the absence of explicit curricular guidelines for addressing the topic. Furthermore, conceptual gaps were identified among a portion of the respondents, who understand pseudoscience as a preliminary stage or a developing science, highlighting weaknesses in epistemological training.
Pseudoscience in teaching: an analysis of the perceptions and attitudes of natural sciences teachers
Keywords: Percepção da pseudociência; Posturas docentes; Ensino de ciências da natureza; Perception of pseudoscience; Teacher stances; Natural sciences education; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade